2014
DOI: 10.1016/j.jagp.2013.12.175
|View full text |Cite
|
Sign up to set email alerts
|

A Multidimensional Home-Based Care Coordination Intervention for Elders with Memory Disorders: The Maximizing Independence at Home (MIND) Pilot Randomized Trial

Abstract: Objectives To assess whether a dementia care coordination intervention delays time to transition from home and reduces unmet needs in elders with memory disorders. Design 18-month randomized controlled trial of 303 community-living elders. Setting: 28 postal code areas of Baltimore, MD. Participants Age 70+, with a cognitive disorder, community-living, English-speaking, and having a study partner available. Intervention 18-month care coordination intervention to systematically identify and address dement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
213
0
7

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 137 publications
(221 citation statements)
references
References 41 publications
1
213
0
7
Order By: Relevance
“…These approaches include but are not limited to the use of innovative technologies to impart education and support (Czaja, Loewenstein, Schulz, Nair, & Perdomo, 2013;Glueckauf et al, 2012), multidisciplinary teams and collaborative primary care models (Callahan et al, 2011), community-based care management models Samus et al, 2014), clinic models (Huang et al, 2013), and interventions that feature a dyadic focus (Whitlatch, Judge, Zarit, & Femia, 2006). This recent ongoing phase also reflects attempts to examine a broader swath of outcomes, translate proven interventions for delivery and sustainability in service contexts Gitlin, Jacobs, & Earland, 2010;Gitlin, Marx, Stanley, & Hodgson, 2015;Nichols, Martindale-Adams, Burns, Graney, & Zuber, 2011), and replicate findings from previously tested interventions with different populations (Gaugler, Reese, & Mittelman, 2013).…”
Section: Framework For Understanding Dementia Caregiving and Intervenmentioning
confidence: 99%
“…These approaches include but are not limited to the use of innovative technologies to impart education and support (Czaja, Loewenstein, Schulz, Nair, & Perdomo, 2013;Glueckauf et al, 2012), multidisciplinary teams and collaborative primary care models (Callahan et al, 2011), community-based care management models Samus et al, 2014), clinic models (Huang et al, 2013), and interventions that feature a dyadic focus (Whitlatch, Judge, Zarit, & Femia, 2006). This recent ongoing phase also reflects attempts to examine a broader swath of outcomes, translate proven interventions for delivery and sustainability in service contexts Gitlin, Jacobs, & Earland, 2010;Gitlin, Marx, Stanley, & Hodgson, 2015;Nichols, Martindale-Adams, Burns, Graney, & Zuber, 2011), and replicate findings from previously tested interventions with different populations (Gaugler, Reese, & Mittelman, 2013).…”
Section: Framework For Understanding Dementia Caregiving and Intervenmentioning
confidence: 99%
“…The trial design and methods have been described previously (22). This 18-month randomized controlled trial included elders with memory disorders living at home (n=303) and their informal caregivers (n=278).…”
Section: Methodsmentioning
confidence: 99%
“…The intervention was developed to be applicable to a diverse group and implementable in a range of community settings (e.g., social service agencies). In a previous report on patient outcomes, we found that those receiving MIND experienced an overall delay in time to transition from home, reduced unmet care needs, and improved quality of life (QOL) compared to a similar group receiving augmented usual care over an 18 month period (22). …”
Section: Objectivesmentioning
confidence: 98%
See 1 more Smart Citation
“…In the fourth, and present phase of caregiver intervention research (2006 to present) there has been greater focus on the full continuum of dementia (i.e., early phase to end-of-life) [21], as well as greater use of innovative technology [25], multidisciplinary teams, collaborative primary care management models [21,[26][27], and dyadic focused interventions [28]. Nonetheless, continuing challenges with ADRD family caregiver interventions need to be addressed, such as translating these interventions and adapting them for integration into a care delivery setting and testing them on a larger scale [21].…”
Section: Caregiver Interventionsmentioning
confidence: 99%